Enhancing Empirical Energy Functions Using Physics- and Machine Learning-Based Extensions Structure, Dynamics and Spectroscopy of Modified Benzenes - Lek Chaton, Kham (Journal of computational chemistry, 2025)
© 2025 The Author(s). Journal of Computational Chemistry published by Wiley Periodicals LLC.